2021
DOI: 10.3390/jpm11050381
|View full text |Cite
|
Sign up to set email alerts
|

Special Attention to Physical Activity in Breast Cancer Patients during the First Wave of COVID-19 Pandemic in Italy: The DianaWeb Cohort

Abstract: Recent evidence highlights that physical activity (PA) is associated with decreased recurrence risk, improved survival and quality of life for breast cancer (BC) patients. Our study aimed to explore patterns of increased/decreased PA, and sedentary behaviors among BC women of the DianaWeb cohort during the first wave of COVID-19 pandemic, and examined the association with residential locations, work changes, different modality used to increase PA, and quality of life. The study analyzed the questionnaires comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
(37 reference statements)
0
15
0
1
Order By: Relevance
“…In this regard, a recent study showed that 90% of physically active BCSs decreased PAL and increased sedentary time [ 33 ]. Moreover, a survey analysis with special attention to understanding the barriers that may influence an active lifestyle in the Italian BC women from the DianaWeb court (781 BC women) underlines the negative impact of the pandemic on MET-min/week of walking, vigorous intensity, and total PA [ 34 ]. On the contrary, our results suggest a relevant increase in the total PAL level, despite home-confinement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a recent study showed that 90% of physically active BCSs decreased PAL and increased sedentary time [ 33 ]. Moreover, a survey analysis with special attention to understanding the barriers that may influence an active lifestyle in the Italian BC women from the DianaWeb court (781 BC women) underlines the negative impact of the pandemic on MET-min/week of walking, vigorous intensity, and total PA [ 34 ]. On the contrary, our results suggest a relevant increase in the total PAL level, despite home-confinement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the age of COVID-19, exercising in gym facilities had the risks for virus transmission through aerosol and surface contact among the exercisers. A recent study showed that BCSs increased sedentary behaviors and decreased PA levels (PALs) during the pandemic lockdown [ 33 , 34 , 35 ]. In these circumstances, it could be useful to adapt the usual methods of exercise delivery to home-based exercise programs [ 27 ] to counteract detrimental effects of home-confinement [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrates the importance and effectiveness of a specific exercise education provided in the hospital, prescribed and supervised by a qualified and specialized exercise trainer, who starts working with the patient at the end of her therapeutic regime and then continues to provide support to help the patient gradually move towards an active lifestyle. Numerous studies have highlighted the low PALs in BC patients at different stages of disease [ 39 ] in clinical and emergency contexts [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Após leitura na íntegra e crítica dos trabalhos selecionados para essa revisão integrativa foi possível identificar quatro categorias de estudos, são elas: 1) Recomendações: nove estudos (Soran, et al, 2020;Al-Shamsi, et al, 2020;ABRAFISM, 2020;Batra, et al, 2021;Rezende, et al, 2020;Macedo, et al, 2020;Curigliano, et al, 2020;Moreno, et al, 2020;Damani, et al, 2020); 2) Prática de atividade física: três estudos (Lyra, et al, 2021;Natalucci, et al, 2021;Pinto, et al, 2020); 3) Aspectos psicológicos: dois estudos (Vanni, et al, 2020e Rossetto, et al, 2021; 4) Impactos nos sistemas de saúde: cinco estudos (Papautsky, et al, 2020;Azar, 2021;Moura, et al, 2021;Araújo, et al, 2020;Busheri, et al, 2021).…”
Section: Resultsunclassified